Biochemical evaluation of Nigella sativa L. seeds on fluconazole toxicity in Wistar rats. Issue 1 (1st January 2020) - Anwar, Firoz; Al-Abbasi, Fahad A.; Nadeem, Muhammad Shahid; Al-Ghamdi, Sharifa; Kuerban, Abudukadeer
Abstract : Nigella sativa L. seed commonly known as black seed, extensively used as a folk medicine in Middle East and Asian subcontinent. Traditionally it is used as an adjunct therapy along with modern medicine to counter the adverse effects. Pure thymoquinone or isolated compounds are not free from adverse effects. The present study was undertaken to evaluate N. sativa seeds powder impact on the fluconazole (FLZ) induced toxicities in the liver and kidneys. Male Wistar rats were acclimatized, divided into four groups each group with six animals. Experimental animals were subjected to an FLZ dose of 50 mg per kg of body mass. The toxic effects of FLZ treatment were manifested and animals were given 1000 mg of N. sativa seeds powder per kg of body weight to observe any retrieval. Dissected animals were evaluated for biochemical and histopathology alterations. Based on findings, it can be concluded that N. sativa seeds powder restored various altered biochemical parameters induced by fluconazole and can be used along with fluconazole in the treatment of fungal infections.